Предмет: Математика,
автор: aleksandrae491
Упростите
X-0,3(2,7 x-1,4x)
Х+0,7*(3,2х-0,6х)
Ответы
Автор ответа:
0
х-0,3*2,7х+0,3*1,4х= х-0,81х+0,42х=0,61х
х+0,7*3,2х-0,7*0,6х= х+2,24х-0,42х=2,82х
х+0,7*3,2х-0,7*0,6х= х+2,24х-0,42х=2,82х
Автор ответа:
0
и все? больше нечего?
Автор ответа:
0
больше нечего, я так понимаю это было 2 выражения
Автор ответа:
0
спасибо))
Похожие вопросы
Предмет: Информатика,
автор: hkshdfjhdf
Предмет: Информатика,
автор: limoka301
Предмет: История,
автор: jane2060
Предмет: История,
автор: gazon1234
Предмет: Математика,
автор: Эврис